The Role of White Support in Predicting Racial Minorities’ Feelings of Inclusion and Retention (Journal of Organizational Psychology, 2021)
The principal objective of the current study is to identify specific strategies that White individuals can employ to support coworkers of color in their workplaces. Thus, we introduced a measure of white support for coworkers of color (WSCC) in which employees of color rated their White coworkers’ openness to learning about sociocultural factors that impact the lives of racial minorities and how they can demonstrate solidarity in promoting racial justice in the workplace. Moreover, in the same sample, we found results consistent with the proposition that increased feelings of inclusion mediates the positive affect of WSCC on retention. It is our hope that these findings will provide a starting point for crafting holistic diversity, equity, and inclusion (DEI) initiatives that provide guidance to those who benefit relatively more from the current power structures on practical ways to authentically support and uplift those who benefit relatively less.
Keywords: organizational psychology; equity; diversity; inclusion; belonging; anti-racism; microaggressions; implicit bias; white fragility; systemic racism; critical race theory